Focal Therapy for Prostate Cancer: Recent Advances and Insights - Francesco Lasorsa; Arianna Biasatti; Angelo Orsini; Gabriele Bignante; Gabriana M. Farah; Savio Domenico Pandolfo; Luca Lambertini; Deepika Reddy; Rocco Damiano; Pasquale Ditonno; Giuseppe Lucarelli; Riccardo Autorino; et al. (Current Oncology)
Focal therapy has emerged as a balanced middle ground aiming to reduce overtreatment and the risk of progression, as well as patients’ distress and anxiety. Focal therapy and partial gland ablation prioritize the precise elimination of the index lesion and a surrounding safety margin to optimize treatment outcomes and lower the risk of residual disease. The paradigm of whole-gland ablation has shifted towards more targeted approaches. Several treatment templates ranging from subtotal and hemiablation to “hockey-stick”, quadrant, and even focal lesion ablation have emerged. Many types of energy may be utilized during focal treatment. First, focal therapy can be grossly classified into thermal vs. non-thermal energy. The aim of this non-systematic review is to offer a comprehensive analysis of recently available evidence on focal therapy for PCa.